2018
DOI: 10.1209/0295-5075/122/61001
|View full text |Cite
|
Sign up to set email alerts
|

Stable finite energy global vortices and asymptotic freedom

Abstract: This work deals with global vortices in the three-dimensional spacetime. We study the case of a simple model with U (1) symmetry and find a way to describe stable, finite energy global vortices. The price we pay to stabilize the solution is the presence of scale invariance, but we have found a way to trade it with an electric charge in a medium with generalized permittivity, which is further used to capture the basic feature of asymptotic freedom.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that captures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that captures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context.…”
Section: Introductionmentioning
confidence: 85%
“…Inspired by the results of [14], in the present work we first consider the field-dependent function as a dielectric function to be governed by a single scalar field. In the sequence, we add an extra scalar field, that modifies both the dielectric function and the dynamical term of the first scalar field in the Lagrange density.…”
Section: (): V-vol 123mentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar context, in the recent work in Ref. [34], it has been used to trade scale invariance with an electric charge that capture the basic feature of asymptotic freedom. It has also been added in Refs.…”
Section: The Modelmentioning
confidence: 99%